Shifting dynamics of Sino-American competition in multi-aligned Middle East - Arfan Mahmood; Muhammad Usman Askari (Heliyon)
The Middle East (ME) is one of the most volatile regions of the world where things can change in the blink of an eye. China, once an ordinary energy customer showing hardly any interest in the politics of the ME, has turned itself into a crucial player in rapidly transforming geopolitical landscape of the ME. The increasing footprints of China in the ME pose challenges to the US interests in the region. This article is an attempt to explore the dynamics of evolving competition between the US and China in the ME. It seeks to find out whether this alarmist narrative that the increasing footprints of China in the ME are a threat to the US interests and regional stability is well-put or obscures the deeper truth that China's increasing influence reflects a growing trend to multi-alignment in the ME. It further looks into the challenges faced by the US to better protect its interests in the face of rising influence of China in the region. This is a qualitative study which utilizes descriptive and analytical approaches to illustrate the dynamics of Sino-American competition in the ME. It is much easier to understand why Middle Eastern states are more attracted towards China as collaborating with a country other than the US helps them to break the shackles of US dependency. The suitable way for the US to solidify its position is through engagement than dominance.